2014
DOI: 10.1371/journal.pone.0090242
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Profile of Phosphatidylinositol in High Spatial Resolution Imaging Mass Spectrometry as a Potential Biomarker for Prostate Cancer

Abstract: High-resolution matrix-assisted laser desorption/ionization imaging mass spectrometry (HR-MALDI-IMS) is an emerging application for the comprehensive and detailed analysis of the spatial distribution of ionized molecules in situ on tissue slides. HR-MALDI-IMS in negative mode in a mass range of m/z 500–1000 was performed on optimal cutting temperature (OCT) compound-embedded human prostate tissue samples obtained from patients with prostate cancer at the time of radical prostatectomy. HR-MALDI-IMS analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 46 publications
3
68
0
Order By: Relevance
“…PIs are not considered to be rate-limiting for the formation of PIP n , and their roles in many cancers are yet to be defined. However, specific PIs have been proposed as biomarkers for prostate cancer (46), and have been shown to be elevated in human lung tumors (47). One possibility here is that PI may provide an alternative source of arachidonic acid, because the most abundant PI identified was arachidonatecontaining PI (38:4).…”
Section: Discussionmentioning
confidence: 99%
“…PIs are not considered to be rate-limiting for the formation of PIP n , and their roles in many cancers are yet to be defined. However, specific PIs have been proposed as biomarkers for prostate cancer (46), and have been shown to be elevated in human lung tumors (47). One possibility here is that PI may provide an alternative source of arachidonic acid, because the most abundant PI identified was arachidonatecontaining PI (38:4).…”
Section: Discussionmentioning
confidence: 99%
“…IMS was previously used to analyze intracellular phospholipids (Shimma et al, 2007;Snel and Fuller, 2010;Miyamura et al, 2011;Kawashima et al, 2013;Goto et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Buck et al (2015) and Groseclose et al (2015) reported localization of SN-38, which is an active metabolite of a colon cancer drug, and deposition of dabrafenib in renal tubules from a toxicological study, respectively. Furthermore, a comparison of endogenous substrates between normal and tumorous tissues (Shimma et al, 2007;Kawashima et al, 2013;Goto et al, 2014), and changes in the endogenous substrates in response to drugs were also examined by IMS (Sun et al, 2016). Therefore, it is possible to evaluate susceptibility to DIPL by distinguishing mouse and human hepatocyte regions on the liver slices prepared from chimeric mice after the administration of amiodarone and analyzing hepatic localization of amiodarone, desethylamiodarone, and PhCs by IMS.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high resolution MSI provided a significant advantage of autoradiography from the aspect of the drug metabolites (Fehniger et al 2011;Jirasko et al 2014;Liu et al 2013;Buck et al 2015) and demonstrated the distribution of a confirmed drug metabolite that possibly lead to the drug toxicity (Török et al 2015). The technology is today making important contributions in fields such as PK screening (Castellino et al 2013), novel pro-drug concepts (Nilsson et al 2010;Fehniger et al 2011), drug delivery systems (DDS) by micellar nanoparticle formulation (Swales et al 2014), biomarkers for PD (Yasunaga et al 2013;Shariatgorji et al 2014;Cobice et al 2013) as well as proteomics (Goto et al 2014;Ye et al 2014). MSI ultimately leads to a better understanding of ADME, PK/PD and TK/TD.…”
Section: Drug Metabolism and Pharmacokinetics (Dmpk)mentioning
confidence: 99%